2023
DOI: 10.1002/smi.3227
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between childhood gender nonconformity, aversive childhood experiences, and mental health in heterosexual and non‐heterosexual cisgender men: The buffering effect of sense of coherence

Abstract: Childhood gender nonconformity (CGNC) seems to be associated with more mental health problems in adulthood. Previous research has suggested that this link might be mediated via the increased risk for aversive childhood experiences (ACEs) as a negative social reaction to CGNC. However, no study yet examined the role of resilience factors in this relationship. The present study aims to address this gap by examining the potential buffering effect of sense of coherence (SOC). In a German sample of 371 cisgender me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 140 publications
(187 reference statements)
0
2
0
Order By: Relevance
“…Most research has assumed that GNC does not drive mental health problems. Rather, negative social experiences following GNC, resulting from prejudice and their consequences, are the source of mental health problems (Issler et al, 2023;Martin-Storey, 2016). Reviews on the relationship between GNC and victimization experiences have suggested a small relationship between the two (Hu et al, PREPRINT -not peer-reviewed 2023; Thoma et al, 2021).…”
Section: Gender Nonconformity Victimization Experiences and Mental He...mentioning
confidence: 99%
See 1 more Smart Citation
“…Most research has assumed that GNC does not drive mental health problems. Rather, negative social experiences following GNC, resulting from prejudice and their consequences, are the source of mental health problems (Issler et al, 2023;Martin-Storey, 2016). Reviews on the relationship between GNC and victimization experiences have suggested a small relationship between the two (Hu et al, PREPRINT -not peer-reviewed 2023; Thoma et al, 2021).…”
Section: Gender Nonconformity Victimization Experiences and Mental He...mentioning
confidence: 99%
“…Reviews on the relationship between GNC and victimization experiences have suggested a small relationship between the two (Hu et al, PREPRINT -not peer-reviewed 2023; Thoma et al, 2021). In addition, primary studies (e.g., Issler et al, 2023;Zhao et al, 2021) investigating this model have found a mediating effect of victimization experiences on the association between GNC and mental health. However, most studies have used a cross-sectional design, so causal conclusions could not be drawn.…”
Section: Gender Nonconformity Victimization Experiences and Mental He...mentioning
confidence: 99%